Determinants of government debt in Malaysia / Siti Nurjihan Musa - Musa, Siti Nurjihan (Faculty of Business and Management, 2020)
This research aims to investigate the determinants of government debt in Malaysia in the period from 1989 to 2019. Each independent variable needs to measure their relationship with the Government Debt (RGD) and the variables are Inflation rate (RIR), Climate Change (RCC) and Government Expenditure (RGE). Based on the Multiple Linear Regression (MLR) result showed that inflation rate has a significant negative relationship towards Government Debt (RGD). However, research identify that the relationship between Climate Change (RCC) and Government Expenditure (RGE) and Government debt (RGD) are insignificant negative relationship. It is founded that lagged debt is included in the model due to changes in the interest rate from the previous accumulated debt may causing the fluctuation value of the debt.